RODINGITES FROM THE ALKALINE ULTRAMAFIC VOLCANICS OF THE VALAGINSKY RANGE, EASTERN KAMCHATKA: PETROLOGIC IMPLICATIONS - Seliverstov V.A.; Osipenko A.B.; Sidorov E.G. (My University, 1999)
New data are reported on the geologic setting, structural relations, and composition of calcsilicate metasomatites (rodingites) found, in association with alkali-ultramafic volcanics, in the northern Valaginsky Range, Eastern Kamchatka. Unique conclusions were derived as to the general formation mechanism of rodingite mineral composition using the example of these high-temperature rocks. The new data were used as a basis for deriving a palingenetic-metasomatic model which extends the thermodynamic range of rodingite genesis. The universal nature of calcium metasomatism in mafic-ultramafic rocks of various associations is demonstrated.